2022
DOI: 10.4293/jsls.2022.00048
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare and Indirect Cost of the Laparoscopic vs. Vaginal Approach in Benign Hysterectomy

Abstract: Background and Objectives: The aim of this study was to analyze indirect costs of vaginal and laparoscopic routes for hysterectomy to determine whether this makes a difference in total costs when considering route for surgery.Methods: A five-year observational retrospective cohort study was conducted in an academic tertiary care center. A total of 517 patients scheduled for total laparoscopic hysterectomy (n = 137) and vaginal hysterectomy (n = 380) for benign conditions between January 1, 2008 and December 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…However, our study showed that was not the case, as blood loss showed lower values in the LSCP group, although this difference did not reach statistical significance. It is plausible that reduced blood loss in case of laparoscopic procedures can be attributed to better visualisation, easier tissue manipulation and access ( 34 , 35 ). Furthermore, the choice of anaesthesia may potentially influence blood loss outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that was not the case, as blood loss showed lower values in the LSCP group, although this difference did not reach statistical significance. It is plausible that reduced blood loss in case of laparoscopic procedures can be attributed to better visualisation, easier tissue manipulation and access ( 34 , 35 ). Furthermore, the choice of anaesthesia may potentially influence blood loss outcomes.…”
Section: Discussionmentioning
confidence: 99%